The Economic Role of the Crown in the Old Babylonian Period - Yoffee, Norman
A Dissertation Presented to the Faculty of the Graduate School of Yale University in Candidacy for the Degree of Doctor of Philosophy; abi ṣābim and mu’errum-officials.